The use of information technology tools for nutritional management - Hammed, Ademola Monsur; Olowolayemo, Akeem; Adewale, Nafeesah (2017)
The respondents do realize the importance IT-enabled food choice system. Although, lack of awareness contributed to the reduced usage of food information from internet, the respondents express intention to use. Even the awareness of respondents about any blog on food choice is still average rate. Therefore users need awareness to read a blog as it works as an effective guideline in utilizing the apps services. Nutrition applications seeking to utilize internet tools in nutrition management should prioritize management tasks to empower users to use resources with more confidence. It is therefore recommended that the people should be reviewed or rather geared towards the use of multimedia and interactive approach.